DALONGDALAM LUKISAN SUREALIS - ALFURQAN BAHRI, Drs. Mediagus, M.Pd., Drs. Efrizal, M.Pd. (Universitas Negeri Padang, 2019)
Acehnese people have costoms and culture that have existed in various caremonies. Every ceremony is held, Acehnese always ase atool called dalong in serving. Dalong is used to place various dishes at each ceremony.The creation of this work aims to express in the flow of surrealism paintings, which dalong has been marganalized by the times. The flos of paintings made is a surrealist style of art, works made are imposibble in reality and lead to visuality in dreams. In the process of making work, produce more different forms of artwork but each work has relevance.Surrealist paintings made on canvas numbered ten works of various sizes and titles, that is 1) Opperessed, 2) Excluded, 3) Not the same again, 4) Banquet, 5) Wainting Time, 6) Pion, 7) Despicable, 8) Outside Influence, 9) Selection, 10) The Latter. In making Dalong-themed artworks, can be useful for students in the future and can generate motivasion and enthusiasm in woeking art, aspecially painting. Key Words:Dalong, Paint